ISOLATED CLUSTERS OF PF CATALOGUE - Panko, E.; Andrievsky, S. (Одеські астрономічні публікації, 2012)
The properties of isolated galaxy clusters are discussed. The clusters were found among 1746 PF clusters inclusive 50 and more galaxies in structure field. For 19 clusters with distances to the nearest neighbour larger than 68.5 h-1 Mpc we assigned the morphological types of these clusters according to Abell and Bauts & Morgan. The existence of preferential planes and angular momenta of isolated clusters was assumed. We connect evolution of isolated clusters with common large-scale characteristics.